1990
DOI: 10.2105/ajph.80.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Workplace health hazards: analysis of hotline calls over a six-year period.

Abstract: Between 1981-1986 a state-based occupational health telephone hotline received more than 8,000 inquiries on over 3,000 hazardous agents. Major caller groups were employees (37%), employers (20%), health care providers, primarily physicians (19%), government agencies (12%), and labor unions (6%). Employees were the fastest growing caller group. Callers inquired about general health hazards of chemicals (65%), the relation of symptoms to work (22%), and risks to pregnancy (13%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…One potential source of counseling might be Teratology Information Services across the United States; but in a 2008 survey, occupational topics only accounted for 6% of their counseling time. 13 Occupational counseling services [14][15][16] have identified a demand for occupational reproductive counseling and the need to increase resource information for women's health providers. The American Congress of Obstetrics and Gynecology (ACOG) and the American Society for Reproductive Medicine (ASRM) recently issued a joint Committee Opinion on the role of reproductive health professionals in the prevention of exposure to environmental and occupational toxic chemicals.…”
Section: Overviewmentioning
confidence: 99%
“…One potential source of counseling might be Teratology Information Services across the United States; but in a 2008 survey, occupational topics only accounted for 6% of their counseling time. 13 Occupational counseling services [14][15][16] have identified a demand for occupational reproductive counseling and the need to increase resource information for women's health providers. The American Congress of Obstetrics and Gynecology (ACOG) and the American Society for Reproductive Medicine (ASRM) recently issued a joint Committee Opinion on the role of reproductive health professionals in the prevention of exposure to environmental and occupational toxic chemicals.…”
Section: Overviewmentioning
confidence: 99%
“…Comparable consultation services in other states are infrequently accessible. An exception is California, which has a telephone hot line that provides information on workplace health hazards including reproductive hazards to workers, employers, the general public, and health professionals (Quint, Handley, & Cummings, 1990). Examples of other resources for public health nurses to enhance their knowledge and skills in the assessment and control of occupational exposures include the National Library of Medicine's MEDLINE database (Bethesda, MD), university-affiliated departments of genetics, the NIOSH (Atlanta, GA), and the 14 NIOSH-funded Educational Resource Centers located in various U.S. academic institutions.…”
Section: Discussionmentioning
confidence: 99%
“…The previous research on health hotlines has demonstrated the signi cant potential of health hotlines in improving citizens' health literacy, conducting public health surveillance and optimizing health resource allocation [2][3][4][5][6] . Analyzing the data from the Shanghai 12320 Health Hotline can provide a comprehensive understanding of residents' true health service needs and the primary issues affecting the health sector in Shanghai.…”
Section: Introductionmentioning
confidence: 99%